2009
DOI: 10.1007/s11033-009-9729-6
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 gene polymorphism in obese patients with insulin resistance

Abstract: IGFs (Insulin like growth factors) are important regulators of pancreatic beta cell development, growth and maintenance. Mutations in the IGF genes have been found to be associated with diabetes mellitus, myocardial infarction obesity. These associations could result from changes in insulin secretion. We aimed to investigate IGF-1 gene polymorphism in obese patients with insulin resistance. We included 100 obese patients with insulin resistance 30 healthy subjects to study. At baseline examinations, antropomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 14 publications
1
18
1
Order By: Relevance
“…In contrast, another study demonstrated that the homozygous carriers ( 4194 bp) among Korean women have higher serum IGF-I levels compared with noncarriers [33]. Fidan et al [10] noted that serum IGF-I level was lower in obese patients with the predominant ( 4194 bp) genotype, in contrast to our findings. However, in accordance with our above-mentioned explanation, other factors such as insulin resistance can affect serum IGF-I level in obesity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, another study demonstrated that the homozygous carriers ( 4194 bp) among Korean women have higher serum IGF-I levels compared with noncarriers [33]. Fidan et al [10] noted that serum IGF-I level was lower in obese patients with the predominant ( 4194 bp) genotype, in contrast to our findings. However, in accordance with our above-mentioned explanation, other factors such as insulin resistance can affect serum IGF-I level in obesity.…”
Section: Discussioncontrasting
confidence: 99%
“…Noncarriers of the 192-bp alleles showed increased relative risk for type 2 diabetes and myocardial infarction [8]. The most frequent IGF-I genotype associated with obesity was the 194 bp genotype [10]. The most frequent IGF-I genotype associated with obesity was the 194 bp genotype [10].…”
Section: Introductionmentioning
confidence: 99%
“…A functional relationship was found between this type of polymorphism and the circulating levels of IGF1. People with the 192 bp allele (19 repeats) or 194 (20 repeats) have higher levels of IGF1 than non-carriers of these alleles 13. Moreover, some studies have shown an association between increased levels of IGF and increased cancer risk 14,15.…”
Section: Introductionmentioning
confidence: 99%
“…The numbers of (CA) repeats vary between 10 and 24, whereby the Caucasian population mostly contains 19 (CA) repeats. 128,129 Genetic architecture of acne vulgaris Among 115 Turkish acne patients and 116 controls, the difference between the group was significant at >194 bp 19 CA repeats (P = 0.0002) (Tasli et al). 130 In a meta-analysis study, the Caucasian population presented a higher frequency of 19 (CA) repeats than the Asian population (65.5 vs. 33.3%) (Chen et al).…”
Section: Insulin-like Growth Factor-1 Gene (Igf-1)mentioning
confidence: 99%